Prototype: Elevated robotic system with three degrees of freedom for hip rehabilitation controlled by embedded systems - Martínez Santos, Antonio Isaías; Buenabad Arias, Héctor Miguel; Blanco Ortega, Andrés; Basurto Pensado, Miguel Ángel; Hernández Cabrera, Diego (Revista Mexicana de Ingenieria Biomedica, 2025)
This article presents the development of a prototype robotic system that allows movements in X-Y-Z axes from an elevated position on the patient, designed specifically for hip rehabilitation. The system, controlled by embedded systems, provides precise and adaptable control to the patient's needs during the rehabilitation process. The structure of the robot allows controlled and adjustable movements, promoting the future integration of routines and exercises that mimic the natural range of motion of the hip. In addition, the system is optimized to be intuitive, ensuring efficiency for both the patient and the healthcare professional, facilitating rehabilitation and improving functional outcomes.